Papel do sistema renina angiotensina no traumatismo cranioencefálico - Caroline Amaral Machado (2023)
Traumatic brain injury (TBI) is any injury directed to the vessels, meninges, brain, or skull, caused by an external mechanical force. TBI mainly affects the economically active age group of the population in developed and developing countries, causing significant socioeconomic impact. The importance of TBI in the public health context has increased strongly in recent years, due to studies that have linked this disease to neuropsychiatric and cognitive deficits that may arise after the traumatic event, such as depression, anxiety and memory and learning impairments. The pathophysiology of TBI is still poorly understood, but it is known that inflammatory processes are related to the development of secondary injuries in this disease. Therefore, we believe that the renin-angiotensin system (RAS) may participate in the pathophysiology of TBI, as well as that the counter-regulatory axis of this system may play a neuroprotective role through the regulation of these inflammatory processes. In this sense, the main objective of the present work is to investigate the role of the RAS in an experimental model of TBI. As well as, characterize the transient and/or permanent cognitive and behavioral changes, associating them with morphological changes and levels of inflammatory mediators after TBI. Furthermore, our proposed study will also allow the identification of potential inflammatory biomarkers, enabling the development of new therapeutic strategies.